2006
DOI: 10.1021/jm0580151
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Efficiency of Diethylene Glycol-Linked Glycoconjugated Porphyrins in Human Retinoblastoma Cells

Abstract: Photodynamic therapy (PDT) is emerging as a new strategy for the conservative treatment of hereditary retinoblastoma. The glycoconjugated porphyrins TPP(p-Deg-O-alpha-GalOH)(3), TPP(p-Deg-O-beta-GalOH)(3), TPP(p-Deg-O-alpha-ManOH)(3), and their S-analogues were synthesized to obtain efficient photosensitizers with some retinoblastoma cell affinity. In these systems, a sugar motif and porphyrin core were linked by a diethylene glycol spacer (Deg). Cellular uptake, localization, and photoactivity have been exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 28 publications
3
103
0
Order By: Relevance
“…The first step towards nano-sized PS formulations were made through the preparation of dendritic [80,81], glyco [82,83], amino acid [84] and peptide [85] functionalized porphyrins. Initially, many of these studies were just aimed at increasing the water solubility, formulation properties and targeting of the PS [86].…”
Section: Ps Linkermentioning
confidence: 99%
“…The first step towards nano-sized PS formulations were made through the preparation of dendritic [80,81], glyco [82,83], amino acid [84] and peptide [85] functionalized porphyrins. Initially, many of these studies were just aimed at increasing the water solubility, formulation properties and targeting of the PS [86].…”
Section: Ps Linkermentioning
confidence: 99%
“…Other linker units may be employed as well. Thus, a library of diethylene glycol linked glycoporphyrins TPP (204)(205)(206) and their S-analogues (207,208) were synthesized and their PDT efficacy tested against retinoblastoma cells [198] . All O-glycosylated diethylene glycol porphyrins and the reference compound (203) were synthesized from 5,10,15-tris(p-phenol)-20-phenylporphyrin and reacted with the bromo-diethylene glycol substituted glycosides followed by deacetylation or with 2-(2-chloroethoxy)ethanol for 203.…”
Section: Glycosidation Reactions O-linked Systemsmentioning
confidence: 99%
“…The non-glycosylated dendron was also coupled with 497 affording 512a,b for comparative biological studies. Taking into account their previous work on glycoporphyrins [160,162,198,204,205,255] they concluded that the best compounds appeared to have three α-glycosyl groups on the paraposition of the meso-phenyl ring via a flexible linker. However, the presence of three sugars via a glycodendrimer decreased the phototoxicity [256] .…”
Section: Dendritic Systemsmentioning
confidence: 99%
See 2 more Smart Citations